PEMODELAN GENERATOR YANG EFEKTIF YANG DIPASANGKAN DENGAN IMPACT WRENCH SEBAGAIUSAHA UNTUK MENINGKATKAN DAYA PADA PEMBANGKIT LISTRIK TENAGA SAMPAH: INTRUMENTATTION AND COMPUTATIONAL PHYSICS - Hubertus Ngaderman; Ego Srivajawaty Sinaga (Prodi Fisika FST UNJA, 2021)
The amount of waste can be overcome, some efforts are needed to reduce it. This research will focus on the numerical model of a solid waste power plant. Researchers replace turbine with an impact which have a specification certain pressure, the impact rotates the generator The purpose of this research is to get the rms voltage of a generator, where the generator is a generator capable of supplying a rms voltage. This effort is made to convert waste energy into electrical energy. Generators which are the main topic in this research are synchronous generators and permanent magnet generators. Water with a mass of requires a temperature of to provide the required stress, while water with a mass of , its temperature is Water with a mass of requires a temperature of to provide the required voltage, while water with a mass of has a temperature of . For a water mass of , a temperature of , the synchronous rotor speed is , the rms voltage is . To reach the rms voltage of , the rotor on the generator must rotate at a synchronous speed of .